Psychohistory and general historical forms of personality in Peru - Paredes Ruiz, Santiago (2008)
The present paper is a synthesis of the theoretical and methodological investigations about the general historical forms of personality in Peru, which is developed from the fields of psychohistory and neurosciences. We propose and develop the category of general historical forms of personality. We explain their development in the evolution of people from Peru, from the prehispanic time, until the republican period, including the colony. The historical and social data of each time are integrated inside a psychological interpretation of the most general patterns of personality. We follow a method of qualitative analysis starting from historical data. From a psychohistoric restructuring, we interrelate and integrate transdisciplinary, neuroscientific, psychological, historical and ethnohistorical constructions. In the conclusions, we stand out the heuristic value of the category general historical forms of personality, for the development of psychohistory, psychology, and social scientist based neurosciences.